2020
DOI: 10.1515/znc-2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction by α-mangostin-loaded nanoparticles in human cervical carcinoma cells

Abstract: The compound α-mangostin (AMG) extracted from Garcinia mangostana L. has potent anticancer properties but its clinical application is limited because of its poor solubility. In this study, AMG-loaded nanoparticles (NMG) were synthesized using a new formula and their apoptosis activity against human cervical carcinoma (HeLa) cells was investigated in comparison with organic solvent-soluble AMG in free form. The NMG was successfully synthesized with a particle size of <50 nm, polydispersity index <0.3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…We found that AM, inhibited in a concentration-dependent manner, cervical cancer cell proliferation, whose responsiveness was as follows: CaSki > SiHa > HeLa > C33a. This agrees with previous studies, where the antiproliferative effect of AM was observed in HeLa and SiHa cells [25,26,28]. Notably, in our research, the most AM sensitive cells were those with the highest number of HPV copies of the most carcinogenic HPV16 subtype, specifically, SiHa and CaSki cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that AM, inhibited in a concentration-dependent manner, cervical cancer cell proliferation, whose responsiveness was as follows: CaSki > SiHa > HeLa > C33a. This agrees with previous studies, where the antiproliferative effect of AM was observed in HeLa and SiHa cells [25,26,28]. Notably, in our research, the most AM sensitive cells were those with the highest number of HPV copies of the most carcinogenic HPV16 subtype, specifically, SiHa and CaSki cells.…”
Section: Discussionsupporting
confidence: 93%
“…Among the natural compounds studied, the xanthone α-mangostin (AM), a phytochemical obtained from the pericarp of mangosteen fruit, exhibits broad biological activities, with outstanding antineoplastic [15] and anti-viral effects [16][17][18][19][20][21][22][23][24]. The antitumor effects of AM, have been widely evaluated in different malignancies [15], including cervical cancer [25][26][27][28]. Additionally, the antiviral activity of AM, has been described against rotavirus [17], hepatitis C virus [24], dengue virus [18][19][20][21], chikungunya virus [23], and SARS-CoV-2 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Mangostin is a series of natural compounds isolated from the epicarp of the fruits of Garcinia Mangostana Linn which is one of the most popular herbal medicines ( Nguyen et al, 2020 ). In traditional Chinese medicine, the fruit hull of mangosteen has been widely used in the treatment of diarrhea, diabetes, and cancer for centuries ( Ittiudomrak et al, 2019 ; Zou et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The infrared spectrum data (Fig. B) showed the incorporation of AMG in the carriers ( Nguyen et al, 2020 ).…”
Section: Methodsmentioning
confidence: 98%
“…AMG loaded polymeric nanoparticles were prepared using Tween 20 (Sigma) and PEG 400 (Sigma) based on a method described by Nguyen et al (2020) NanoAMG was characterized using a dynamic light scattering machine (DLS - HORIBA SZ-100 analyzer, Germany). The nanoparticle sizes were in a range of 10–50 nm with a zeta potential value of − 35.20 mV and a polydispersity index (PI) was < 0.3 (Fig.…”
Section: Methodsmentioning
confidence: 99%